2001
DOI: 10.1159/000052614
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Glomerular Expression of Agrin in Diabetic Nephropathy and Podocytes, Cultured in High Glucose Medium

Abstract: Aim: A decrease in glomerular heparan sulfate (HS) proteoglycan (PG), without apparent decrease in HSPG core protein expression, has been reported to occur in diabetic nephropathy (DN). In most studies however, agrin, the major HSPG core protein in the glomerular basement membrane, has not been studied. This prompted us to study the glomerular expression of agrin in parallel to the expression of HS-glycosaminoglycans (GAG) in biopsies of patients with DN. Furthermore, the influence of glucose on agrin producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
(60 reference statements)
1
24
0
1
Order By: Relevance
“…The concentration of agrin, the major protein core of heparan sulphate proteoglycan, was found to be decreased in the GBM in renal biopsies from patients with diabetic nephropathy. The same phenomenon was observed in vitro, in podocytes cultured in the presence of high glucose, indicating downregulation of the expression of heparan sulphate proteoglycan [24]. It is rather likely that the reported HSPG changes in diabetes are not limited to the kidneys, since reduced HSPG expression was also observed in basement membranes in the skin, in patients with type 1 diabetes suffering from diabetic nephropathy [25].…”
Section: Glomerular Basement Membrane (Gbm)supporting
confidence: 63%
“…The concentration of agrin, the major protein core of heparan sulphate proteoglycan, was found to be decreased in the GBM in renal biopsies from patients with diabetic nephropathy. The same phenomenon was observed in vitro, in podocytes cultured in the presence of high glucose, indicating downregulation of the expression of heparan sulphate proteoglycan [24]. It is rather likely that the reported HSPG changes in diabetes are not limited to the kidneys, since reduced HSPG expression was also observed in basement membranes in the skin, in patients with type 1 diabetes suffering from diabetic nephropathy [25].…”
Section: Glomerular Basement Membrane (Gbm)supporting
confidence: 63%
“…This was assessed by immunostaining using antibodies JM-403 and NAH46 that recognize specific HS structures in the GBM. The former has been used to demonstrate the loss of GBM-HS in human and experimental kidney disease, including human membranous nephritis, lupus nephritis, minimal change disease, and diabetic nephropathy 14,39,50 and rat adriamycin nephropathy and Heymann nephritis. 51,52 Although these studies support the theory that reductions in GBM-HS contribute directly to loss of barrier function, labeling with mAb JM-403 was recently reported to be normal in diabetic humans and rats with microalbuminuria, and it was concluded that loss of GBM-HS may be a secondary event that occurs in advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…39 Here, normal fetal mouse kidney was stained with a panel of three different antisera raised against the C terminus of agrin. Each gave the same pattern, labeling the BM and vascular cleft of S-shaped nephrons and pre-capillary loopstage glomeruli (Figure 2A).…”
Section: Agrn Knockout Mice Synthesize N-terminal Truncated Forms Of mentioning
confidence: 99%
“…Synthesis of proteoglycans occurs in all three glomerular cell types, but podocytes are an especially important source of these negatively charged molecules. Proteoglycan synthesis in podocytes is differentially influenced by high ambient glucose and ANG II (83,84); high glucose suppresses the production of agrin's core protein, whereas ANG II decreases synthesis of the core protein and diminishes the sulfation of its side chains (83,84). Podocytes exposed to ANG II decrease the amount of HSPG on their cell surfaces and in the extracellular matrix (83); these results may partly explain the antiproteinuric effect of ACE inhibitors and angiotensin receptor blockers in diabetic nephropathy.…”
Section: Role Of Heparan Sulfate Proteoglycansmentioning
confidence: 99%